Benzodioxane‐Benzamides as Antibacterial Agents: Computational and SAR Studies to Evaluate the Influence of the 7‐Substitution in FtsZ Interaction. (11th December 2019) - Straniero, Valentina; Sebastián‐Pérez, Victor; Hrast, Martina; Zanotto, Carlo; Casiraghi, Andrea; Suigo, Lorenzo; Zdovc, Irena; Radaelli, Antonia; De Giuli Morghen, Carlo; Valoti, Ermanno
Abstract: FtsZ is a crucial prokaryotic protein involved in bacterial cell replication. It recently arose as a promising target in the search for antimicrobial agents able to fight antimicrobial resistance. In this work, going on with our structure‐activity relationship (SAR) study, we developed variously 7‐substituted 1, 4‐benzodioxane compounds, linked to the 2, 6‐difluorobenzamide by a methylenoxy bridge. Compounds exhibit promising antibacterial activities not only against multidrug‐resistant Staphylococcus aureus, but also on mutated Escherichia coli strains, thus enlarging their spectrum of action toward Gram‐negative bacteria as well. Computational studies elucidated, through a validated FtsZ binding protocol, the structural features of new promising derivatives as FtsZ inhibitors. Abstract : Keeping it together : Herein we summarize our recent findings in the SAR of a series of benzamide inhibitors of the prokaryotic cell division protein FtsZ. The proposed compounds exhibit promising activity against Gram‐positive and Gram‐negative strains, including multidrug‐resistant bacteria. We also validate a FtsZ binding protocol and highlight the key structural features for the optimal interaction with the target protein.